2013
DOI: 10.1017/s1355771812000258
|View full text |Cite
|
Sign up to set email alerts
|

The Naturalised and the Surreal: changes in the perception of popular music sound

Abstract: In a musical context, the word ‘sound’ implies a set of sonic characteristics. Within popular music, this notion of sound sometimes supplies the very identity of a tune, a band or a musician. Sound is often conceptualised as a virtual space and in turn compared to actual spatial environments, such as a stage or an enclosed room. One possible consequence of this tendency is that this virtual space can become utterly surreal, displaying sonic features that could never occur in actual physical environments. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Born’s critique is valuable, but it is important to consider other engagements with space-form that suggest alternative perspectives. Although space-form can certainly be understood as the ‘language’ or ‘tonality’ of electroacoustic composition, Brøvig-Hanssen and Danielsen have shown that it is also a pivotal aspect of commercial music production (Brøvig-Hanssen and Danielsen 2013: 72). In the digital era, popular music producers generally and EDM producers in particular have often moved beyond Euclidean types of ‘mix space’ or ‘the sound-box’ (Dockwray and Moore 2010) by creating spatial environments that defy normative boundaries, or by conjuring various types of spatial surrealism (Brøvig-Hanssen and Danielsen 2013: 73).…”
Section: Reflections On Smalley’s Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Born’s critique is valuable, but it is important to consider other engagements with space-form that suggest alternative perspectives. Although space-form can certainly be understood as the ‘language’ or ‘tonality’ of electroacoustic composition, Brøvig-Hanssen and Danielsen have shown that it is also a pivotal aspect of commercial music production (Brøvig-Hanssen and Danielsen 2013: 72). In the digital era, popular music producers generally and EDM producers in particular have often moved beyond Euclidean types of ‘mix space’ or ‘the sound-box’ (Dockwray and Moore 2010) by creating spatial environments that defy normative boundaries, or by conjuring various types of spatial surrealism (Brøvig-Hanssen and Danielsen 2013: 73).…”
Section: Reflections On Smalley’s Theorymentioning
confidence: 99%
“…Yet a relatively unexplored question is whether spectromorphology and space-form might be relevant to musics beyond the electroacoustic sphere. Recently, Smalley (2016) has used some of his terms to describe sound-shapes in French Baroque music, whilst Brøvig-Hanssen and Danielsen (2013, 2016) have drawn upon Smalley’s work in relation to popular music production. These developments hint at the possibility of a re-orientated, hybrid framework.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of form, rhythm and harmony may assist in drawing distinctions between the various styles, however, a more relevant focus may be the manner in which trip hop artists manipulate the sonic and spectral elements of their work. This is not to diminish the significant musicological differences that exist within trip hop, however, it is the sound that can identify a tune, band, or musician (Brøvig-Hanssen and Danielsen 2013).…”
Section: Style Analysismentioning
confidence: 99%
“…Spatial properties can reflect actual physical environments that the listener relates to a previously experienced space, such as a room or concert hall, or they can reflect artificial spaces that do not exist in nature. Artificial spaces can become surreal to the extent that ‘what is heard departs from the convention for normal sound production within a particular context’ (Brøvig-Hanssen and Danielsen 2013: 75). Smalley develops six categories to discuss the spatial style of a work, two of which are pertinent to this analysis.…”
Section: Style Analysismentioning
confidence: 99%
“…Personal music listening has been framed as a means of escaping everyday reality, with listeners engaging in solitary encounters with recorded music they choose, immersing themselves in sonic, narrative worlds (Bull, 2003(Bull, , 2012Quinones, 2013;DeNora, 2000). Such escapist listening habits may be understood not simply as the imagined projecting of one's self into another context, but also as instances of embodied aural-spatial perception -of sensing one's own presence within and in relation to a virtual environment, with its own implied dimensions, material characteristics, contents and inhabitants (Moore, 2010;Lacasse, 2000;Brøvig-Hanssen & Danielsen, 2013, 2016. Such an understanding is supported by recent theories of everyday listening and environment, which emphasise auditory experience as the perception of 360-degree space in relation to a listener's embodied self, as the inhabiting of environmental reality (LaBelle, 2016;Voegelin, 2014;Salter, 2019).…”
Section: Introductionmentioning
confidence: 99%